Adverse Selection and Liquidity Distortion - Chang, Briana (Review of Economic Studies, 2018)
This article develops a tractable model with two-dimensional asymmetric information in asset markets: sellers are privately informed about their asset quality and distress positions. Illiquidity arises endogenously and manifests itself through two distinct market outcomes. The first outcome features limited market participation, resulting in a dry-up in trading volume. The second outcome involves a large volume at a depressed price. Only in the latter outcome do distressed sellers engage in fire sales, quickly unwinding their positions at a steep price discount. The article further establishes that this equilibrium can arise only when buyers expect that sellers with a higher need for immediacy will on average have higher-quality assets. Hence, both the information structure and the distribution of sellers’ distress are crucial for the existence of fire sales.